2023
DOI: 10.21873/invivo.13057
|View full text |Cite
|
Sign up to set email alerts
|

4D FlowVersus2D Phase Contrast MRI in Populations With Bi- and Tricuspid Aortic Valves

Abstract: Aim: To compare 4D flow magnetic resonance imaging (MRI) and 2D phase contrast (PC) MRI when evaluating bicuspid (BAV) and tricuspid (TAV) aortic valves. Materials and Methods: A total of 83 subjects (35 BAV, 48 TAV) were explored with 4D flow and 2D PC MRI. Systolic peak velocity, peak flow and regurgitation fraction were analysed at two pre-defined aortic levels (aortic root, midtubular). Furthermore, the two methods of 4D flow analysis (Heart and Artery) were compared. Results: Correlation between the 2D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…There are numerous studies regarding the validation of 4 D flow MRI sequences against 2 D flow MRI in vivo showing no significant differences between 2 D flow MRI and 4 D flow MRI, and excellent correlation between both techniques with a correlation coefficient of up to R = 0.98 has been found [13,16,17]. Contrary to those results, other groups reported that 4 D flow MRI significantly underestimates systolic peak flow velocities, while 2 D flow MRI gives accurate results [18,19]. Other groups found significant underestimation of aortic or pulmonary regurgitation and intracardiac flow when using 4 D flow MRI measurements [20][21][22].…”
Section: Discussionmentioning
confidence: 95%
“…There are numerous studies regarding the validation of 4 D flow MRI sequences against 2 D flow MRI in vivo showing no significant differences between 2 D flow MRI and 4 D flow MRI, and excellent correlation between both techniques with a correlation coefficient of up to R = 0.98 has been found [13,16,17]. Contrary to those results, other groups reported that 4 D flow MRI significantly underestimates systolic peak flow velocities, while 2 D flow MRI gives accurate results [18,19]. Other groups found significant underestimation of aortic or pulmonary regurgitation and intracardiac flow when using 4 D flow MRI measurements [20][21][22].…”
Section: Discussionmentioning
confidence: 95%